microRNA-670 modulates Igf2bp1 expression to regulate RNA methylation in parthenogenetic mouse embryonic development - Hao, Jindong (Sci Rep, 2020)
Aberrant epigenetic modification, including N(6)-methylation of adenosine (m6A), has been frequently reported in embryos derived from parthenogenetic activation (PA). However, the role of Igf2bp1 expression pattern in m6A modification and the mechanism through which Igf2bp1 function is regulated in PA embryos remains elusive. Therefore, in this study, using si-Igf2bp1 and betaine (N,N,N-trimethylglycine, a major methyl donor), we investigated the effect of Igf2bp1 expression in m6A modification on the development of PA embryos. The results indicated that the down-regulation of Igf2bp1 reduced the cleavage and blastula rates of PA embryos. Moreover, m6A expression level was markedly down-regulated following microinjection with si-Igf2bp1. However, the treatment with betaine could significantly restore the m6A level. Further bioinformatics analysis revealed Igf2bp1 as the putative target of microRNA 670 (miR-670). Thus, to confirm this finding, mimics and inhibitor of miR-670 were microinjected into PA embryos. The results demonstrated that miR-670 inhibitor augmented the expression of Igf2bp1 and rescued cleavage and blastula rates. In addition, the miR-670 inhibitor promoted the m6A expression level. TUNEL assay revealed a loss of expression of Igf2bp1 induced cell apoptosis in PA embryos. Taken together, these results demonstrated that miR-670-3p functions as the regulator of Igf2bp1 expression and plays a crucial role in PA development through m6A modification.